Focus Group Interviews in Child, Youth, and Parent Research: An Integrative Literature Review. Issue 1 (7th November 2019) - Adler, Kristin; Salanterä, Sanna; Zumstein-Shaha, Maya
Focus groups are becoming increasingly popular in research, especially in parent and child research. Focus group interviews allow participants to tell their own stories, express their opinions, and even draw pictures without having to adhere to a strict sequence of questions. This method is very suitable for collecting data from children, youths, and parents. However, focus group interviews must be carefully planned and conducted. The literature on focus group interviews with adult participants is extensive, but there are no current summaries of the most important issues to consider when conducting focus group interviews with children, youths, or parents. This article outlines the use of focus groups in child, youth, and parent research and the important factors to be considered when planning, conducting, and analyzing focus groups with children, youths, or parents.